2013
DOI: 10.1017/s1047951113000590
|View full text |Cite
|
Sign up to set email alerts
|

Mitro-aortic aneurysms in children: single-centre experience and review of the literature

Abstract: Pseudoaneurysm of the mitral-aortic intervalvular fibrosa is a rare but potentially fatal anomaly. In our experience, surgical cure was achieved for the majority of the cases, except for a case for which infection could not be locally eradicated, leading to multiple reinterventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…[1][2][3] Pseudoaneurysm formation has also been reported as a "congenital" diagnosis in cases where preceding infection, trauma, or surgery have not been documented. [4][5][6][7][8] Gelehrter et al 4 reported seven patients with pseudoaneurysms originating from the aorto-mitral intervalvular fibrosa. All except one patient had associated CHD, preceding cardiac intervention, infection, or trauma.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Pseudoaneurysm formation has also been reported as a "congenital" diagnosis in cases where preceding infection, trauma, or surgery have not been documented. [4][5][6][7][8] Gelehrter et al 4 reported seven patients with pseudoaneurysms originating from the aorto-mitral intervalvular fibrosa. All except one patient had associated CHD, preceding cardiac intervention, infection, or trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Successful repair was first described by Waldhausen et al . in 1966 13 , and we have demonstrated several cases of successful resection in children (Cases 1–3 and 6–8) 6,10 . Clinicians should monitor asymptomatic patients closely for pseudoaneurysm enlargement and encroachment of nearby structures, as well as associated thrombus formation and rupture.…”
Section: Discussionmentioning
confidence: 76%
“…Pseudoaneurysm of this area is rare and has been reported mostly in adult patients following trauma, cardiac surgery or endocarditis 1,3 . Several case studies have described its occurrence in children following cardiac surgery 4,5 or endocarditis 6,7 , with few case reports describing the congenital nature of these pseudoaneurysms 5,6,[8][9][10] . Prenatal diagnosis of pseudoaneurysm of the MAIVF indicates that this abnormality can be congenital.…”
Section: Etiology and Pathophysiologymentioning
confidence: 99%
“…References of all included articles were searched for any additional reports. There were a total of 46 pediatric patients aged 0–21 years in 35 reports, including our case 1–34 . P‐MAIVF cause was assigned based on the original authors of the reports.…”
Section: Resultsmentioning
confidence: 99%